A perspective of biometric, visual and refractive outcomes of cataract surgery: a report of an ophthalmologist in compulsory governmental service - Yesilkaya, Elif Ceren (The European Research Journal, 2020)
Objectives: Knowledge of normal values of biometric parameters in cohort and relationships of them is helpful for ophthalmologists who want to achieve successful results. The aim of this study is to define these parameters in the light of experiences of an individual cataract surgeon after her residency program.Methods: This is a retrospective, register-based study. Preoperative biometric and postoperative refractive data including axial length (AL), mean keratometry (K), anterior chamber depth (ACD), astigmatism, lens thickness (LT) of 310 patients who had cataract surgery were reviewed. Ultrasound and optical biometry were used to evaluate the biometric parameters of the eyes.Results: 0.5 D of refractive target (RT) was obtained in 52.1% (186 eyes) of eyes, 1.0 D of RT in 82.20% (293 eyes) and 2.0 D of RT in 98.3% (351 eyes). Analyses of visual acuity show that 43.7% and 86.3% of eyes reached 0.00 and 0.30 log MAR or better. Age, ACD, LT, AL, preoperative corrected distance visual acuity, preoperative astigmatism and preoperative K were correlated between each other significantly (p < 0.001). The longer AL was found associated with older age (β = .745, p = 0.003), and lower K (β = -0.327, p < 0.001). A significant association between K value and older age (β = .680, p = .029) and shorter AL (β = -.660, p < 0.001) was seen.Conclusions: These data show the normative parameters of biometry values for the Turkish population. These results may be helpful in calculating intraocular lens power and evaluating refractive error for young ophthalmologists who have to work with ultrasound biometry in compulsory service.